Numerical study of heat transfer, pressure drop and entropy production characteristics in inclined heat exchangers with uniform heat flux using mango bark/CO2 nanofluid - Okwesilieze Uwadoka; Adekunle O. Adelaja; Olabode T. Olakoyejo; Opeyemi L. Fadipe; Steven Efe (Heliyon, 2023)
For sustainable low-carbon cities, using sustainable urban energy system solutions is imperative. CO2-based bionanofluid is one proposed energy system solution that is sustainable and environmentally friendly. This paper examines the thermal-hydraulic and entropy production properties of mango bark/CO2 nanofluid for industrial-inclined gas cooling applications. The influence of gravitational force (in terms of tube inclination angle), volume fraction, and Reynolds number on the heat transfer, pressure drop, and entropy production of CO2-based mango bark nanofluids in laminar flow through a circular aluminum tube are numerically studied. The bionanofluid flows through a tube with an inner radius of 2.25 mm, a length of 970.0 mm, and an initial temperature of 320.0 K. A constant heat flux of −10.0 W/m2 is applied to the flow at its walls. The laminar flow regime with Reynolds numbers of 100, 400, 700, and 1000 are subjected to flow inclinations of ±90°, ±60°, ±45°, ±30°, and 0° and bionanofluid volume fractions of 0.5%, 1.0%, and 2.0%. Results show that ±45° tube inclination angle offers the optimal heat transfer coefficient, maximum pressure drop, and minimum total entropy production rates for Re > 100; however, for Re = 100, these occur at the inclination angle of −30° and +60°. The pressure drop shows less sensitivity to the inclination angle; however, it offers peak values at the same inclination angles as the heat transfer coefficient for the respective Reynolds number values. The maximum thermal enhancements due to gravitational effect are 42%, 93.98%, 121.28%, and 150% for Reynolds numbers of 100, 400, 700, and 1000, respectively, while that due to nanofluid volume fraction are less than 16%.